2013
DOI: 10.1021/ie303275e
|View full text |Cite
|
Sign up to set email alerts
|

Physico–Chemical Processes Limiting CO2 Uptake in Concrete during Accelerated Carbonation Curing

Abstract: Accelerated curing of fresh concrete using CO 2 is a possible approach for value-added, high-volume usage products from waste CO 2 emitted from stationary sources. The extent of CO 2 uptake and the spatial distribution of the CaCO 3 (s) precipitates formed during accelerated carbonation curing of compacted, 4-h hydrated cement mortar (fresh concrete mixture with fine aggregates) samples were investigated in this study. The maximum carbonation efficiency achieved was 20% of the theoretical uptake. Microprobe im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Based on preliminary tests, the demoulded sediment block samples (after 24-h initial casting) was pre-dried at 50 • C for 24 h to reduce the moisture content to 4% for ensuring sufficient pathway for gas penetration, because the dissolution of CO 2 gas and deposition of CaCO 3 on the porous surface could be the limiting factors [41,42]. However, it was noted that elevated temperature may accelerate cement hydration and affect final strength [43], thus the moisture content should be controlled by curing in a drying chamber at room temperature in future studies.…”
Section: Binder Formulation Pretreatment Curing Method and Aggregamentioning
confidence: 99%
“…Based on preliminary tests, the demoulded sediment block samples (after 24-h initial casting) was pre-dried at 50 • C for 24 h to reduce the moisture content to 4% for ensuring sufficient pathway for gas penetration, because the dissolution of CO 2 gas and deposition of CaCO 3 on the porous surface could be the limiting factors [41,42]. However, it was noted that elevated temperature may accelerate cement hydration and affect final strength [43], thus the moisture content should be controlled by curing in a drying chamber at room temperature in future studies.…”
Section: Binder Formulation Pretreatment Curing Method and Aggregamentioning
confidence: 99%
“…Many factors affect the effectiveness of ACC, such as the concentration of CO 2 , temperature, relative humidity, pressure in the carbonation chamber, exposure duration to CO 2 , the age of concrete when exposed to CO 2 , type and amount of binders, and water/cement ratio (Fernández Bertos et al 2004;Chen et al 2011;El-hassan et al 2013;Mohammed et al 2014;Shao & Monkman 2006;Zhan et al 2013a;Zhan et al 2013b). Kashef-Haghighi and Ghoshal (2013) found that CO 2 uptake could be increased significantly through the use of cements having higher amounts of reactive minerals and more fineness, which would provide a higher reactive surface area. Carbonation shrinkage resulting from ACC can be reduced by incorporating mineral admixtures such as slag (Monkman & Shao 2010).…”
Section: Mechanical Properties Durability Characteristics and Shrinkmentioning
confidence: 99%
“…So it is hard to validate the proposed penetration-reaction carbonation model using existing theoretical and numerical models. With regard to experiments, some research has been conducted though experimental investigations in order to develop a carbon dioxide mitigation technology [25,26]. The concrete is used to store carbon dioxide under high CO 2 pressure.…”
Section: Mass Transfer Of Carbon Dioxide In Concretementioning
confidence: 99%